Public Speaking Dalam Konteks Etika Advokat - Nila Trisna; Putri Kemala Sari; Dara Quthni Effida; Arfriani Maifizar; Safrida Safrida; Yeni Sri Lestari (Universitas Teuku Umar, 2020)
Start at the most prestigious and prospective profession. Advocates have an important place in the business world. Apart from being a law enforcer, Advocates are also the only consultants who are relied on and trusted in solving a case at trial. In the provisions of the laws and regulations on Advocates, it is stated that the advocate profession is a profession that is tasked with providing legal services for clients. The activities and scope of activities carried out by Advocates on a daily basis require that Advocates have public speaking skills. Because the ability of an advocate to defend his client is also very much determined by his verbal / speaking skills (Public Speaking). The purpose of implementing this activity is for participants to understand the role and function of Advocates, Advocate code of ethics and the function of additional skills such as public speaking to Advocates. The implementation method is used through the socialization of the Advocate Law, the Advocate's code of ethics and the public speaking function in carrying out the role of an Advocate. The results of the implementation achieved were that participants understood the role, authority and position of an advocate, the scope of the advocate and indicators of public speaking and the use of public speaking.